An analysis and evaluation of the role of the Tambon Council in rural development : a case of Central Thailand - Tasnee Suthinark; Hwang, M.C.; Exell, Robert H.B.; Kammeier, Hans Detlef; Australian Government (Bangkok : Asian Institute of Technology, 1976)
The study is an analysis and evaluation of the Tambon Council's role in rural development. The purpose of the study is to analyze the Tambon Council's important functions, the interrelationship between the central government, the Tambon Council and the village and to evaluate the Program for Rural Development and Provision of Jobs for Rural People in terms of its effectiveness, efficiency, people participation in decision-making and socio politico-economic impacts. Data analysis was based on field data collected from the four Tambon Councils ·in Ang-thong and Petchburi provinces, central Thailand. The study result shows that the Tambon Council's important functions are not very related to development activities and little time is devoted to them. There is still a communication gap between t he villagers, Tambon Council Committee, and government officials since the communication flow which exist is only one-way. Popular support on the Tambon Council is also necessary and important for the Tambon Council Committee to work effectively, The program for rural development and provision of jobs for rural people indicated a number of rural development effects. The program showed that the Tambon Councial who is the key operater of the program performed effectively, but less efficiently when compared to its previous performances. On the analysis of economic impact, the program provides more backwash effect than spread effect ; however, the trickling down benefits which remain in the local communities are higher than any other Tambon development projects which had been done in the past . There are also a number of socio political impacts resulting from the program. It is also found that this program is, however, now saturated and needs to be changed to other types of rural development programs. The reviewing of the Tambon Council' s important functions and authority is suggested. Above all, a single national local coordinated development plan is urgently needed to overcome the problems and constraints.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Sc.) - Asian Institute of Technology, 1976
Keywords: Rural development -- Thailand